Optimal loan portfolio (A case study of Atweaban Rural Bank, Duayaw Nkwanta) - Kwarteng, Ernest (2011)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of a Master of Science degree in Industrial Mathematics